The Importance of Presenting Historical Sources in Historical Research Activities: Pentingnya Menghadirkan Sumber Sejarah Dalam Kegiatan Penelitian Sejarah - Kusdiana, Ading (PT. Student Rihlah Indonesia, 2024)
The purpose of this research is to analyze the importance of presenting historical sources in historical research activities. This research uses a qualitative approach and literature study method. Based on the research results, the existence of historical sources in historical research activities is very necessary, because they will determine the results of historical research. A historical researcher will try to obtain as many historical sources as possible. This is of course very important to do because it will determine the weight and quality of the results of historical research. The more credible sources used, the more weighty the research results will be. On the other hand, the fewer credible sources used, the less weight and quality the research results will be. The presence of primary sources and secondary sources is very necessary in historical research activities. Searching for primary sources in historical research activities needs to be given priority, because a historical work that uses a lot of primary sources has a higher value than secondary sources.